The developing mouse coronal suture at single-cell resolution - Farmer, DT; Mlcochova, H; Zhou, Y; Koelling, N; Wang, G; Ashley, N; Bugacov, H; Chen, H-J; Parvez, R; Tseng, K-C; Merrill, AE; Maxson Jr, RE; et al. (Springer Nature, 2021)
Sutures separate the flat bones of the skull and enable coordinated growth of the brain and overlying cranium. The coronal suture is most commonly fused in monogenic craniosynostosis, yet the unique aspects of its development remain incompletely understood. To uncover the cellular diversity within the murine embryonic coronal suture, we generated single-cell transcriptomes and performed extensive expression validation. We find distinct pre-osteoblast signatures between the bone fronts and periosteum, a ligament-like population above the suture that persists into adulthood, and a chondrogenic-like population in the dura mater underlying the suture. Lineage tracing reveals an embryonic Six2+ osteoprogenitor population that contributes to the postnatal suture mesenchyme, with these progenitors being preferentially affected in a Twist1+/−; Tcf12+/− mouse model of Saethre-Chotzen Syndrome. This single-cell atlas provides a resource for understanding the development of the coronal suture and the mechanisms for its loss in craniosynostosis.